Articulações territoriais: uma cartografia da atenção à população em situação de rua - Magalhães, Julia Araujo [UNESP] (2015)
The attention to the social vulnerable and homeless people demands devices for qualifying the intervention of technical teams in Public Policy. This is an important challenge for the field of mental health, considering the principles of universality, equity and comprehensive care of the Brazilian health system - SUS. Intersectoral coordination is crucial in this field because social assistance is an area which has extensive experience working with this population. Besides, given the fragility of the links between hostels and health facilities, it is difficult to ensure continuity of health care of this population, with high mobility, low institutionalization and housing and documentation multiple conditions. In order to increase the knowledge of existing practices in this field, we made a cartography of the actions of the Consultório na Rua Program agents. Cartography helps us analyze local discourses, explore the boundaries and map lines of flight, which lead us to glimpse other modes of care and life creeping with other forms of composition with power. Field research was conducted at the primary care service in the center of São Paulo. The research made possible to question this health promotion practices, with their specificities and peculiarities, and identify the strengths of both subjugation and standardization as the emancipatory inventive and autonomous participation. There is a description of work agents processes, which can create a clinical work: visits to the field, and analysis of the concept of territory and the way it crosses the health care of this population; reception; meetings. Ana analysis of the objectives and working conditions; and connections and tensions with other departments. We conclude that this program and the agents perform a clinical work because their practice involves an important listening function and bonds with...